“PENDEKATAN BIMBINGAN KEAGAMAAN DALAM PENGUATAN KEIMANAN TERHADAP MUALLAF (STUDI KASUS PADA KLIEN “R” DI PERUMAHAN DARUSSALAM KABUPATEN MUARA ENIM ).” - Desi Ardelawati; Aminullah Cik Sohar (Ghaidan: Jurnal Bimbingan Konseling Islam dan Kemasyarakatan, 2018)
This research explores the new and unfamiliar situation of converts. Therefore the convert is in a position of need guidance about the teachings of Islam. In general, religious guidance provides a positive influence on society, especially the convert. Religious guidance on strengthening the faith of believers is considered important because the faith is the driving force of one's life in running the religion and belief. Faith or belief is a spiritual force that becomes the basis of life activities. This study aims to firstly, discuss the problems or problems faced by the convert client "R" post conversion of religion. Secondly, to see how religious activity converts client "R". Third, to examine how the approach of religious guidance in strengthening the faith to the "R" client's conversion. The research method used in this research is qualitative by using data analysis method of case study Robert K Yin. Robert K Yin shares three analytical techniques for case studies: pattern matching, explanation, and time series analysis. The data used can be obtained by the method of observation, interview and documentation. Informants in this study consisted of four people including clients "R", mentors from clients, community leaders and religious leaders. From the results of research obtained from the observation and interview are: First, the problem or problem faced by the convert client "R" post-conversion of religion after the client decided to become a convert he experienced various problems that come after each other, such as family problems, tranquility, adaptation in running the teachings of Islam and disolidaritas social environment. But the client is able to pass all the exams patiently and the client instills in her that she must be strong, God is testing her strength. Secondly, concerning the problem of the client's religious activity in improving his faith, the client carries out the religious activities that exist in the teachings of Islam, not just the obligatory religious activities which he undertakes but the sunnah as well. Religious activities related to Allah SWT and with the social environment of fellow human beings. Thirdly, the process of religious guidance on the client "R" goes well and gives a positive influence on client's faith. This can be seen from the understanding of the client about the teachings of Islam, the implementation of increased client worship, enthusiasm and enthusiasm of clients in science and attitude and behavior change (akhlakul karimah) in everyday life that the client showed.